Academic stress and suicidal ideation in MDCAT repeating candidates: mediating role of depression and moderating role of age and gender - Bilal, Ahmad; Riaz, Anum (Pakistan Journal of Physiology, 2020)
Background: This study aims to find out the mediating role of depression and moderating role of age and gender in suicidal ideation in response to academic stress among Medical & Dental Colleges Admission Test (MDCAT) repeating candidates in Pakistan. Methods: This was a cross-sectional survey-based study conducted at campuses of Knowledge Inn Preparatory School (KIPS), at Bahawalpur and Multan from Feb to Jun 2018. The sample comprised of 102 MDCAT repeating candidates. Three questionnaires (a) Demographic Information Questionnaire (b) Depression, Anxiety, Stress Scale-21, and (c) Scale for Suicidal Ideation were administered to get the responses of MDCAT repeating candidates. Results: There was a significant mediating role of depression (IE=0.64, SE=0.12, 95% LL=0.40, 95% UL=0.88) in relationship between academic stress and suicidal ideation. There was a significant moderating effect of age (-0.36, SE=0.17, p=0.04, 95% LL= -0.71, 95% UL= -0.01) and non-significant moderating effect of gender (-0.19, SE=0.31, p=0.52, 95% LL= -0.82, 95% UL=0.42) on relationship between academic stress and suicidal ideation respectively. Conclusion: There is a mediating role of depression and moderating role of age in suicidal ideation in MDCAT repeating candidates. Psychological counselling for thwarting the risk of suicidal ideation in MDCAT repeating candidates on periodic basis is recommended. Pak J Physiol 2020;16(3):7–10